Individual taste preferences and excessive body weight of children - Sobek, Grzegorz; Mazur, Artur (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Eating habits and customs are formed at an early age, and they play a special role in the prevention of overweight and obesity. Accepting something as food is largely determined by food preferences. Forming food and taste preferences is particularly intensive in early childhood. Sensory vulnerability of taste recognition apparatus is a personal trait that can influence the perception of food products and everyday food choices. A preference for sweet or fat taste may contribute to an increase in eating food of high energy density that can run overweight risk. Yet, the mechanism that gives people various taste sensitivity, various food preferences, and react differently to eaten food, remains unclear. Undoubtedly taste preferences are one of many factors that determine overweight and obesity among children and adolescents. However, a reverse relationship may be suggested here, i.e. taste preferences are a result of obesity.